INTEGRATING GEOENZO-BASED ETHNOMATHEMATICS TO IMPROVE ELEMENTARY STUDENTS’ MATHEMATICAL CONNECTION ABILITY - Eliterius Sennen; Maximus Tamur; Fersianus Jula; Yuliana Jeliman; Hardianus Arson (Program Studi PGSD Universitas Flores, 2026)
The development of digital technology offers strategic opportunities to improve the quality of mathematics learning in elementary schools, particularly by strengthening students' relatively weak mathematical connection skills. This study aims to test the effectiveness of using ethnomathematics-based GeoEnzo digital demonstration media in improving elementary school students' mathematical connection skills through contextual and meaningful learning. The study used a quasi-experimental design with a pretest–posttest control group. The research subjects consisted of an experimental group that received learning using ethnomathematics-based GeoEnzo media and a control group that followed conventional learning. The research instrument was a mathematical connection ability test that had been validated by experts and met reliability criteria. Data analysis was carried out using a mean difference test and Hedges' g to calculate the effect size and determine the strength of the intervention's influence. The results showed that the increase in students' mathematical connection skills in the experimental group was significantly higher than in the control group, with a Hedges' g value of 0.83, which is classified as a large effect. The increase in ability was seen in connections among mathematical concepts, with other disciplines, and with everyday life contexts. These findings confirm the effectiveness of integrating digital media and ethnomathematics and provide empirical and conceptual contributions as a basis for further research at broader levels, in materials, and in mathematical abilities.